Analysis of Green Effect in Thermal Environment - Ohashi, M.; Harada, T.; Kaneko, D.; Hino, M. (PROCEEDINGS OF HYDRAULIC ENGINEERING, 1996)
The temperature decrease in thermal environment by green effect due to latent heat release has been measured and analyzed at two places in Tokyo area; Tama campus of Chuo University and Kitaterao electric power substation, Kawasaki. Surface temperature of plant canopy layer was lower about 5°C compared with the wall temperature of a neighboring building and with temperature of paved road, and was held almost constant irrespective of the temporal changes in humidity and velocity of surrounding air flow. Temperature of wall and road wetted by pouring water on them decreased to the level of leaf temperature of plant. The fact shows that the green effect is due to the latent heat release by evapotranspiration.